Rechristening the Zabo integrated farming system to the Ruza integrated farming system practised at Kikruma village of Nagaland, India (Indian Journal of Traditional Knowledge (IJTK), 2024)
Kikruma village in the Phek district of Nagaland state is known for its integrated traditional farming system termed Zabo (which means impounding rainwater) for paddy cultivation in terrace fields by the Chakhesang tribe. A visit was conducted by a team of researchers from ICFRE-Rain Forest Research Institute, Jorhat, Assam to Kikruma village in September 2021, when during an interaction with a progressive farmer Mr. Zanehu Tunyi, it was informed that the term Zabo farming has been popularly used by the researchers and exists in the literature, however, the term Ruza is more appropriate for this integrated traditional farming system. A research article “Zabo: A time-tested integrated farming system practised by Chakhesang Tribe of Nagaland” published in the year 2018, reported that the term Zabo is also known as Dzüdü or Ruza system in certain areas of the Phek district. During the visit, the team of researchers from the ICFRE-Rain Forest Research Institute observed that Zabo and Ruza terms are used for two different types of ponds constructed for different purposes. The progressive farmers of Kikruma village explained the farming processes practised in their region. He suggested popularizing the Zabo farming as the Ruza farming system owing to the reasons that the actual water harvesting ponds used for paddy cultivation are known as Ruza in their local area and dialect instead of Zabo. The term Zabo is mainly used for small ponds or pits dug for rearing fish and fish fingerlings during the dry season.